Vagina obscura : an anatomical voyage - Gross, Rachel E. (W.W. Norton & Company, 2022)
"A scientific journey to the center of the new female body. The Latin term for the female genitalia, pudendum, means "parts for which you should be ashamed." Until 1651, ovaries were called female testicles. The fallopian tubes are named for a man. Named, claimed, and shamed: Welcome to the story of the female body, as penned by men. Today, a new generation of (mostly) women scientists is finally redrawing the map. With modern tools and fresh perspectives, they're looking at the organs traditionally bound up in reproduction-the uterus, ovaries, vagina-and seeing within them a new biology of change and resilience. Through their eyes, journalist Rachel E. Gross takes readers on an anatomical odyssey to the center of this new world-a world where the uterus regrows itself, ovaries pump out fresh eggs, and the clitoris pulses beneath the surface like a shimmering pyramid of nerves. Full of wit and wonder, Vagina Obscura is a celebratory testament to how the landscape of knowledge can be rewritten to better serve everyone"--